Recent advances in understanding and managing urolithiasis [version 1; referees: 3 approved] - Walter L. Strohmaier (F1000Research, 2016)
During the last few years, there has been relevant progress in both understanding and managing urolithiasis. Our knowledge of stone formation has changed; although the importance of urine biochemistry was questioned by several investigators years ago, the decisive role of cellular processes (induced by oxidative stress) and the renal papilla has only recently been generally accepted as the most important step in stone formation. For calcium oxalate urolithiasis, the formation of papillary calcifications plays a key role and is of prognostic relevance. Further research has to concentrate on these aspects of preventing urolithiasis. Stone prevention (metaphylaxis) is a major issue when considering the burden it places on healthcare systems. An effective metaphylaxis could lower the cost of stone therapy significantly. For uric acid urolithiasis, so far there is only preliminary information available showing that papillary plaques are not as important as they are in calcium oxalate urolithiasis. Concerning stone management, endourology has improved stone therapy significantly during the last few years. Morbidity decreased and success (stone-free) rates increased. Therefore, the indications for extracorporeal shockwave lithotripsy (ESWL) narrowed. ESWL, however, still has its place in stone therapy. There is not one single treatment modality that is equally effective for all situations. It is important to observe the differential indications for different stones depending on size, localization, and composition.